1944
DOI: 10.1029/tr025i006p00901
|View full text |Cite
|
Sign up to set email alerts
|

Movement and deposition of sediment in the vicinity of debris‐barriers

Abstract: Accelerated erosion and the scour and deposition of sediment in streams have had, in many instances, harmful effects on the use of valley‐floors as residential areas and for farming and grazing. Perhaps the outstanding significance of streams carrying a relatively large sediment‐load is the effect on the silting of large reservoirs, the silting‐rates of which determine not only the life of these reservoirs for flood‐control purposes, but also the perpetuity of agriculture, cities, and industries, which are dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1948
1948
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Engineering guidelines typically suggest that structures should be spaced such that the upstream structure does not interfere with the deposition zone of the next downstream structure (Heed and Mulich, 1973). Approximate spacing can be determined by extending a line from the top of the first downstream structure at the equilibrium slope upstream until it intersects the original streambed (Johnson and Minaker, 1944), thus defining the length of the deposition zone upstream from the structure (Mussetter, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Engineering guidelines typically suggest that structures should be spaced such that the upstream structure does not interfere with the deposition zone of the next downstream structure (Heed and Mulich, 1973). Approximate spacing can be determined by extending a line from the top of the first downstream structure at the equilibrium slope upstream until it intersects the original streambed (Johnson and Minaker, 1944), thus defining the length of the deposition zone upstream from the structure (Mussetter, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Mussetter (1982) showed that the optimum spacing should be the length of the deposition above the structure that is a function of the deposition slope ( Figure 6.12). Figure 6.12 also illustrates the recommendations of Johnson and Minaker (1944), that the most desirable spacing can be determined by extending a line from the top of the first structure at a slope equal to the maximum equilibrium slope of sediment upstream until it intersects the original streambed. However, each of the above references implicitly includes a specific sediment supply concentration, and that concentration is necessary for rational designs.…”
Section: Effectiveness Of Grade Control Structuresmentioning
confidence: 99%